PENATAAN SISTEM DRAINASE DI PRONA 1 KELURAHAN PEMURUS BARU KOTA BANJARMASIN - M. Rif’at HR., M. Ruslin Anwar, Surjono (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2014)
Prona 1 is a residential area which consist of a series of traditional houses called “Rumah Panggung” in swamp area. Eventhough the houses have long and high form but in this swamp area flood and and puddle are happen a lot in Prona 1. This observation process initiated by spreading questionaire to find out about the people’s participation, identify and evaluate the current condition of drainage infrastructure in Prona 1, calculating how severe the damage in swamp area such as lot filling activity, lot hedging and blocking the water access toward water absorption under the high house (rumah panggung), based on those datas will be found out theswamp damage level and plan of drainage building in each sub system. After that we set the calculation of budget plan to build the drainage building. Next step is every variables on each sub system are being calculaterd by using AHP method with Criterium Decision Plus verse 3.0 to determine which sub system has highest priority to built its drainage system. The observation result shows that the participation of people in Prona 1 of drainage function and system is in quite high level. Prona 1 is lack of drainage building, most of it are water channel in various condition since there was no drainage system planning when the neighbourhood built. The damage level in swamp area like lot-filling can be considered as low, although there are many lot-filling, and most of them are for public facility. In the plan, it i needed to provide a channel in lot which have been hedged and blocked from water access and install the water channel in it. Sub system which its drainage system need to be built in prior is Sub System 3 next is SS2, SS5, SS1 and SS4.Keyword: drainage system, swamp area damage, rumah panggung